The effects of anesthesiologist residency on mortality of patients in ICU in Imam Khomeini teaching hospital of Mazandaran Medical University, Sari (2000 – 2004) - B. Mohseni Saravi; E. Bagheriyan Farah Abadi; A. Zamani Kiasari; A. Kabirzadeh; F. Hasanzadeh Kiabi (Journal of Mazandaran University of Medical Sciences, 2006)
Background and purpose: Anesthesiologists have become the first priority since they can play an important role in crisis situations to support respiratory and cardiac urgencies. In this survey, the effects of the resident anesthesiologists were studied on the death of patients having been hospitalized in the Intensive Care Unit of Imam Khomeini training and treatment center, Sari from 2000 to August 2004.Materials and Methods: In this survey, the subjects of the "case group" (passed-away patients during the residency of the anesthesiologist) have been compared to the subjects of the "control group" (having no resident anesthesiologist). The following variables were considered for analysis: age, gender, hospitalization reasons, the original ward, reason of and the service of reference to the Intensive Care Unit, the cause of death, hospitalization period in the original ward and Intensive Care Unit, as well as the number of the visits paid by anesthesiologist. Other interfering variables (such as facilities) were not taken into account, since they had been the same for both groups. Data were analyzed using the SPSS software and the descriptive and analytical (X2,Z,T) statistical tests.Results: The findings of this survey showed that men have died more than women (61.9% vs 38.1%) in the intensive care unit. The total hospitalization period reduced from 14 to 11 days, having an anesthesiologist residing in this ward. It was revealed that the presence of an anesthesiologist reduced the death rate from 24% to 14%.Conclusion: According to the findings of this survey, it has been revealed that the presence of an anesthesiologist can have an outstanding effect on the reduction of the death rate. It is taken for granted that choosing patients must be done in accordance with Classic Indications since there are limited number of beds in ICU and the admission request for different patients. In equal situations, those patients who have better opportunity and less mortality probability and better prognosis in this unit have priority.